2002
DOI: 10.1177/0091270002424009
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Safety of Galantamine in Subjects with Hepatic Impairment and Healthy Volunteers

Abstract: The objective of this study was to compare the pharmacokinetics and safety of galantamine in subjects with hepatic impairment with those in healthy subjects. This was an open-label study in which a single oral 4-mg dose of galantamine was administered to volunteers with mild (Child-Pugh score of 5-6, n = 8), moderate (Child-Pugh score of 7-9, n = 8), or severe hepatic impairment (Child-Pugh score of 10-15, n = 1) and to healthy, matched control subjects (n = 8). Galantamine pharmacokinetics and safety (adverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Currently, the most widely employed biological sample preparation methodologies included protein precipitation (PPT), liquid-liquid extraction (LLE), and solid phase extraction (SPE). Several analytical methods for determining galanthamine in biological fluids have been reported [13,14,20] . Nirogi et al extracted galanthamine from plasma samples using toluene as the extraction solvent in the LC-MS/MS method [13] , and Verhaeghe et al reported that adding 0.1 mol/L sodium hydroxide and a saturated potassium chloride solution can extract galanthamine from plasma samples using toluene in the LC-MS/MS method [14] .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the most widely employed biological sample preparation methodologies included protein precipitation (PPT), liquid-liquid extraction (LLE), and solid phase extraction (SPE). Several analytical methods for determining galanthamine in biological fluids have been reported [13,14,20] . Nirogi et al extracted galanthamine from plasma samples using toluene as the extraction solvent in the LC-MS/MS method [13] , and Verhaeghe et al reported that adding 0.1 mol/L sodium hydroxide and a saturated potassium chloride solution can extract galanthamine from plasma samples using toluene in the LC-MS/MS method [14] .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is important to assess any effects of reduced hepatic function on the pharmacokinetic profile of the drug. The issue is highlighted in a clinical trial by Zhao et al (2002). For patients with moderate hepatic impairment, the pharmacokinetic parameters were very similar to those in healthy patients.…”
Section: Pharmacokinetic Profile Of Galanthamine In Patients With Hepmentioning
confidence: 93%
“…Cytochrome P450 (CYP) 2D6 and 3A4 are the major CYP isoenzymes involved in the hepatic metabolism of this drug. CYP2D6 is responsible for the formation of O-desmethyl-galantamine, and CYP3A4 is involved in the production of galantamine N-oxide [13,14].…”
Section: Introductionmentioning
confidence: 99%